(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
Rapid urban population growth and widespread urbanization are common occurrences in the modern world. They cause several negative repercussions among which Urban Heat Island (UHI) is the most widely recorded occurrence. The population of Dhaka city has increased by 12.64 million from 2011 to 2021 and the temperature by 0.57ᵒ C in the recent decade. Therefore, the city is facing increased public health-related problems associated with high temperatures, outbreaks of diseases, and scarcity of safe drinking water. Considering these matters, this study explores the spatiotemporal changes in Land Surface Temperature (LST) over the last twenty years and the present condition of heat islands. The city was found 3.9 °C warmer than the surrounding rural areas in 2022. The results also show recurring fluctuations in temperature together with a positive change in temperature during the study period. A year of high temperatures follows a gradual decrease in temperatures in the next two years, and a year of low temperatures follows several gradual increases in temperature. It is expected from the result that the upcoming two years (2023 and 2024) will be warmer than the last three years. The findings may provide insight into how LST and UHI fluctuate and aid in developing strategies to lessen their negative consequences. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 1-19